3. x - y +3z= 5
4x + 2y - z=0
-x+3y+z=5 solve using Cramers rule
Answers
Answered by
4
Answer:
3)w – 2x + 5y – 3z = 0; -3w + 6x + Y + Z = 0; 2w – 4x +3y – Z = 3. Use ... 4x +3y – z = 3. Use Cramer's rule method in solving the following systems: ... 5) 14x – 2y - 4z = 0; 18x – 2y -6z = 0; 4x + 8y -14z = 0.
Imagewww.coursehero.com › file › Practi...
Step-by-step explanation:
follow me Piimnfuuu f right now I have a great day of my way home from each other for t the same
Similar questions
Social Sciences,
5 months ago
History,
5 months ago
Science,
10 months ago
Math,
10 months ago
Hindi,
1 year ago